Discrimination of curanderos in the tradition «Las brujas de Ica» - Montalvo Saba, Carolina (2020)
This article will analyse «Las brujas de Ica», a text that forms part of the sixth series of the Tradiciones peruanas, a work by the illustrious writer Ricardo Palma, in which he creates an analogy between two situations separated by time but which are closely related. Firstly, the discrimination or rejection of the Holy Inquisition towards everything that was unknown, especially that related to the medicine of the time, considering it «witchcraft»; and secondly, the current discrimination of the figure of the healer by some doctors, who reject all types of alternative medicine, considering it invalid, lacking sufficient scientific evidence or dangerous.